Comentario sobre el libro de Shoichi Sato: "The Merovingian accounting documents of Tours: form and function", Early Medieval Europe, 2000, 9: 143-161. - Hernández Esteve, Esteban (De Computis, Revista Española de Historia de la Contabilidad., 2004)
Comentario sobre el libro de Shoichi Sato: "The Merovingian accounting documents of Tours: form and function", Early Medieval Europe, 2000, 9: 143-161.